Peningkatan Kemampuan Mengenal Bentuk Melalui Permainan Twister Geometri di TK As-Sayyidi - Pebriani Syahpitri, Anti; Syukri Sitorus , Ahmad (Generasi Emas, 2024)
This research aims to improve the ability to recognize shapes through geometric twister games at As-Sayyidi Kindergarten. The classroom action research method used in this research is the Kemmis & Mc Tagaart model which consists of planning, implementation, observation and reflection.  Data collection techniques use observation and documentation. The research subjects were 14 children, namely 8 boys and 6 girls. The results showed that there were 6 children who completed the pre-cycle with a percentage of 42.8%, in cycle I this increased to 8 children with a percentage of 57.1%, and in cycle II it increased to 12 children with a percentage of 85.7%. Based on the research results, it can be concluded that through the geometric twister game, children at As-Sayyidi Kindergarten can improve their ability to recognize shapes.